Samtaler mellom profesjonelle og barn som har psykisk syke eller rusavhengige foreldre Et etisk og narrativt perspektiv - Grimsgaard, Cathrine (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"This scholarly monograph is based on a doctoral dissertation, On Holding Part of a Child's Life in One's Hands. Conversations between Professionals and Children with Mentally Ill or Substance Addicted Parents: An Ethical and Narrative Perspective, the subject of which is children's participation in group therapy discussions for children whose parents are mentally ill or substance users. The book builds on experiences from participant observation in seven different groups and follow-up conversations with the participating children and the professionals who lead the groups. The objective was to investigate the possibilities children have in such groups for being independent subjects in search of and making sense. The issue is: How are a child's experiences handled in discussion groups for children of mentally ill or substance addicted parents? The book's scientific anchor is in expository hermeneutics, which underpins the emphasis on the significance of balance and reciprocity in interactions between the children and the professionals who lead the groups. In this connection, exploring in concrete situations how the group leader created space for the individual child's perspective by putting his/her own perspectives into play (or by not doing so) is central. Expository hermeneutics also makes possible identifying some of what is not put into words, barely mentioned or implied, in interactions between the professional and the child, but which nonetheless may have considerable bearing on the understanding that is formed. The experiences and observations from the discussion groups are conveyed via nine stories detailing specific conversations and activities in which the children conveyed their experiences, thoughts and feelings, without them becoming further topics in the group work. Through interpretation of these stories a perception emerges of group conversation for children with mentally ill or addicted parents as being a practice in which the child's own experience of their parent's illness or dependency is only to a limited degree made an issue. Through a theoretical discussion in which what has transpired in the group interactions is elevated to a more generally insightful level, a deeper understanding of this phenomenon is sought."